Impact of Personality on Pet Ownership Among Residents of Brgy. Pasong Putik, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to discover the personality traits of the pet owners in Brgy. Pasong Putik,Quezon City, by utilizing the Big Five Personality Traits. This study will mainly identify andassess the impact of personality on pet ownership, as well as the factors that affect the petowner's personality in terms of companionship, social support, and animal welfare. This studyis limited to fifty (50) male and female pet owners between the ages of 18 - 25 (young adults).Agreeableness got the highest weighted mean (x = 3.60) with the verbal interpretation“moderately accurate.” Consciousness got the second to the highest weighted mean (x =3.24), Openness to Experience got a 3.23 weighted mean, Extraversion got a 2.93 weightedmean, and lastly, Neuroticism got the lowest weighted mean (x = 2.88) with the same verbalinterpretation of “neither inaccurate nor accurate.” The overall weighted average mean scoreof 3.49 showed that the respondents “strongly agreed” with pet companionship, socialsupport, and animal welfare.According to the findings of this study, the majority of respondents are males who scoredhighly in the personality trait "Agreeableness," while "Neuroticism" received the lowest scoresresiding in Brgy. Pasong Putik, Quezon City. The respondents also "strongly agreed" with petcompanionship, social support, and animal welfare as determining the factors of personalitytraits of the pet owners.
Keywords: Psychology